An introduction to the Medipix family ASICs. (August 2020) - Ballabriga, R.; Campbell, M.; Llopart, X.
Abstract: The first Medipix chip which aimed at permitting single photon counting on a sizable matrix of pixels was developed in the mid-1990's. In the following 20 years two families of chips have evolved from that initial effort. The Medipix photon counting family of chips comprises Medipix, Medipix2 and Medipix3. A 4th generation chip, Medipix4, is under development. The Timepix chips were initially more aimed at single particle detection and that family comprises Timepix, the most recent Timepix2 chip (introduced in this Special Issue) and Timepix3. The 4th generation Timepix4 is also under development and a first version will be produced in 2019. This paper seeks to provide a brief introduction to the various members of the Medipix family and provide references to more detailed descriptions already available in the literature.